2015
DOI: 10.1109/tpami.2014.2353644
|View full text |Cite
|
Sign up to set email alerts
|

Projection Operators and Moment Invariants to Image Blurring

Abstract: In this paper we introduce a new theory of blur invariants. Blur invariants are image features which preserve their values if the image is convolved by a point-spread function (PSF) of a certain class. We present the invariants to convolution with an arbitrary N-fold symmetric PSF, both in Fourier and image domain. We introduce a notion of a primordial image as a canonical form of all blur-equivalent images. It is defined in spectral domain by means of projection operators. We prove that the moments of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 76 publications
0
15
0
1
Order By: Relevance
“…Instead of metrics, there are works which propose blur-invariant/robust representations. Among these are moment invariants described by Flusser et al [9] for symmetric blur kernels, which are further shown to be Point clouds Symmetric functions [20] complete. They also combine the proposed blur invariant with illumination and rotation invariance.…”
Section: Examples Of Factors Of Variation and Associated Invariantsmentioning
confidence: 99%
“…Instead of metrics, there are works which propose blur-invariant/robust representations. Among these are moment invariants described by Flusser et al [9] for symmetric blur kernels, which are further shown to be Point clouds Symmetric functions [20] complete. They also combine the proposed blur invariant with illumination and rotation invariance.…”
Section: Examples Of Factors Of Variation and Associated Invariantsmentioning
confidence: 99%
“…HU [25] apresentou em sua teoria, uma possibilidade capaz de realizar a descrição de figuras geomé-tricas planas com base nos momentos invariantes bidimensionais [26,27,28].…”
Section: Extração De Característicasunclassified
“…Highly compressed information about the object, even if it has been extracted from a blurred image without any restoration, could be sufficient provided that the features used for object description are not much affected by blur. This idea was originally proposed by Flusser et al [4,5,6,12] who introduced so-called blur invariants with respect to non-parametric centrosymmetric and N -fold symmetric h. For Gaussian blur, first heuristically derived blur invariants were proposed by Liu and Zhang [10]. Later on, Zhang et al [15] proposed a distance measure between two images which is independent of a circular Gaussian blur.…”
Section: Introductionmentioning
confidence: 99%